Young Writers and the Tradition in Philippine Short Fiction in English: Does the force exist or is the Jedi Council Pulling our Legs - Montes, Timothy R. (Silliman Journal, 2022)
The paper tackles the problematic of establishing a definable tradition for the Philippine short story in English. From the point of view of a creative writer, establishing a tradition in the genre is as fuzzy as defining the Force in Star Wars. The canon in Philippine short story in English was established by the academe and young fiction writers, most of them college-educated, emerged from the country's institutions of higher learning. Nevertheless, despite the consensus that several short story writers are significant, crea-tive writers themselves are wary of defining althe tradition in this genre. Of more relevant concern is how young writers can break away from the Anglo-American tradition of modernism in fiction. The paper ends with the answers of three contemporary young writers to questions about their awareness of a literary tradition in the genre they are working in.